Fittingness 2022
DOI: 10.1093/oso/9780192895882.003.0012
|View full text |Cite
|
Sign up to set email alerts
|

Well-Being as Fitting Happiness

Abstract: There is an intuitive connection between well-being and happiness. Accordingly, many theories of well-being hold that well-being consists in (either unqualified or properly qualified) happiness. Traditional happiness-based theories are subject, however, to several important objections. The goal in this chapter is to offer a new happiness-based theory that is immune to the main objections raised against traditional happiness-based theories. The authors’ own fitting happiness theory of well-being can be seen as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Previous research showed that the effectiveness of behavior in religious coping can help a person manage individual feelings of distress and anxiety because it can overcome guilt, adhere to God's will or destiny, view suffering in a positive light, and help control individual fear (Chatard et al 2020;Rosmarin & Leidl 2020;Vishkin & Tamir 2020). Rossi and Rossi (2017) reported that religious coping correlated negatively with emotion regulation difficulties, especially regarding lack of emotional clarity, inability to accept negative emotions, and difficulty regulating emotions in general (Rossi & Rossi 2017). From the Islamic perspective, Islamic religious coping indicates an individual's connection with God and dependence on God for everything in life as coping for reducing anxiety and depression and restoring hope (Achour et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research showed that the effectiveness of behavior in religious coping can help a person manage individual feelings of distress and anxiety because it can overcome guilt, adhere to God's will or destiny, view suffering in a positive light, and help control individual fear (Chatard et al 2020;Rosmarin & Leidl 2020;Vishkin & Tamir 2020). Rossi and Rossi (2017) reported that religious coping correlated negatively with emotion regulation difficulties, especially regarding lack of emotional clarity, inability to accept negative emotions, and difficulty regulating emotions in general (Rossi & Rossi 2017). From the Islamic perspective, Islamic religious coping indicates an individual's connection with God and dependence on God for everything in life as coping for reducing anxiety and depression and restoring hope (Achour et al, 2017).…”
Section: Introductionmentioning
confidence: 99%